Manajemen Toko Buah Musliha Di Krian Sidoarjo Terhadap Produk Olahan Buah Ditinjau Dari Hukum Bisnis Syari’ah - Silvi Maslahatul Ummah; Norma Fitria (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Fruit is one of the items that is widely sold on the market and fruit is also a profitable trade. However, fruit has a drawback, namely that the quality of the fruit itself does not last long or rots quickly. The management used at the shop is to minimize losses due to fruit that is not suitable for consumption so that it becomes processed and gets a high selling price, namely by reprocessing it into juice, fried foods and chili sauce. This research aims to: (1) find out and examine the management of the Musliha fruit shop in Krian Sidoarjo regarding processed fruit products that use fruit that is less suitable for consumption, (2) examine the review of sharia business law on the management of the Musliha fruit shop in Krian Sidoarjo regarding processed products fruit that uses fruit is less suitable for consumption. This research is empirical juridical research, with a conceptual approach and analyzed using inductive and descriptive methods. Primary legal materials from observations, interviews, documentation, library data. Secondary law is obtained from books, journals and related literature. The results of the research show that the Musliha Fruit Shop's management of fruit that is not suitable for consumption has been running well and in accordance with sharia principles and social responsibility. This shows that the shop has implemented business practices that comply with sharia law principles, which include halal products, fairness in business and social responsibility. By continuing to maintain and improve the quality of products and services, Musliha Fruit Shop can continue to develop and make a positive contribution to the surrounding environment. This evaluation not only provides an overview of product halalness and fairness in business, but also about the shop's social responsibility in the context of sharia law.